Parkinson’s Disease: A Narrative of the Evolving Understanding of the Role of α-Synuclein in Screening - Alan D. Kaye; Kassady A. Perkinson; Noah J. Spillers; Alexis J. Vega; Caylin J. Roberts; Evan M. Downs; Melissa M. Sheth; David W. McGregor; Shahab Ahmadzadeh; Jibin Mathew; Sahar Shekoohi (Current Issues in Molecular Biology)
The present investigation aims to examine the role of α-synuclein seed amplification assays for screening Parkinson’s disease. Parkinson’s disease (PD) is a debilitating neurodegenerative disorder caused by the loss of dopaminergic neurons in the midbrain, leading to symptoms such as tremors, bradykinesia, postural instability, dementia, and depression. It is classified as an α-synucleinopathy related to the role of α-synuclein aggregates in neuron degeneration. Diagnosis relies on clinical assessment without premortem diagnostic tests or imaging, often resulting in delayed detection and impaired symptom management. In this regard, our study explores a screening technique using an amplification assay to measure α-synuclein levels in cerebrospinal fluid, which could potentially identify early pathological changes and improve diagnostic accuracy and patient outcomes. While preliminary results are promising, further studies are needed to evaluate this approach’s accuracy and clinical feasibility. A review of numerous trials demonstrates that α-synuclein seeding amplification assays (SAA) are a highly reliable, sensitive, and specific diagnostic tool for PD. This assay offers a promising opportunity to improve early diagnosis and quantify severity, especially for asymptomatic individuals or those with a family history of PD, allowing for earlier intervention and more effective disease management. In summary, the emerging body of evidence supporting α-synuclein as a biomarker should allow patients with PD to be detected and treated sooner, enhancing patients’ quality of life and potentially changing the disease trajectory.